The Implementation of the Cooperative Learning Model Type Think Pair Share (TPS) on Eighth Grade Students in Terms of Student Self-Confidence - Nasrulloh, Muhammad Farid; Khoiron, Aris; Zuhriawan, Muhammad Qoyum; Hidayatulloh, Faisol (APPLICATION: Applied science in Learning Research, 2024)
This study aims to determine the relationship between the application of the Think Pair Share (TPS) cooperative learning model and the improvement of self-confidence among eighth-grade students at SMPI Ar-Rahman Perak. The research method used is a pre-experimental design with a one-group pretest-posttest design and a quantitative research approach. The subjects of this study are the eighth-grade students at SMPI Ar-Rahman Perak. The research instruments used are tests and non-tests. The test instruments include pretest and posttest essay questions, as well as a self-confidence questionnaire to measure the students' self-confidence after the application of the Think Pair Share (TPS) model. The non-test instrument used is an interview with the mathematics teacher of the eighth grade at SMPI Ar-Rahman Perak to understand the implementation of the learning process in the classroom. The data analysis technique used is hypothesis testing. Before conducting hypothesis testing, the data obtained were first subjected to normality and homogeneity tests. Based on the calculation of the paired sample t-test, the significance value obtained is 0.003. This significance value indicates 0.003 < 0.05, thus it can be concluded that Ha is accepted. The acceptance of Ha means that there is a difference in the level of self-confidence among the eighth-grade students at SMPI Ar-Rahman Perak before and after the application of the Think Pair Share (TPS) learning model.